Analysis Of Elementary School Teachers Perceptions Regarding The Implementation Of The Independent Curriculum - Albar, Mauliyah; Setya Nugroho , Arya (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
The changing curriculum makes it difficult for teachers to carry out evaluations which are too complicated and lack facilities to support the learning process.This change feels confusing for teachers. This research uses a qualitative descriptive methodology with a case study type of research which is an attempt to describe and analyze a particular example. Even though case studies are usually specific, this does not prevent their application in a larger social context. The subjects in this research were 5 teachers at UPT SD Negeri 110 Gresik to find out the teachers' opinions or points of view regarding the implementation of the Merdeka curriculum at UPT SD Negeri 110 Gresik. From the results the researcher found that teachers still face obstacles in implementing the Merdeka curriculum, namely (1) there are still Some teachers are still confused about preparing teaching modules (2)There are still many teachers who experience difficulties in organizing summative assessments.(3.) The solution to these obstacles is that further investigation is needed to create an action plan that has the potential to overcome the obstacles faced by educators in implementing the Independent Curriculum.. The benefit of this research is knowing teachers' perceptions regarding the preparation, implementation and evaluation of the independent curriculum.